Urban Conservation Of Historical Touristic Sites - Hussein, Fatma (LAP LAMBERT Academic Publishing ·, 2019)
This book contains the research done for the fulfilment of the requirements for the award of the degree of Master of Science in Architecture Engineering and Environmental Design at the Arab Academy for science and Technology and Maritime Transport. The book covers all the cultural heritage, architectural and urban conservation definitions, theories and charters. Also, it contains some analytical examples for different urban conservation practices. Finally, the book discusses the case study of Abu-Qir urban district in Alexandria, Egypt showing all the treasures and potentials that this area posses, focusing on the presence of fortifications and their urban context in terms of the relation between urban conservation and tourism. Ending with recommendations and guidelines for urban conservation practices in historical touristic sites.